Bank Risk Taking, Credit Booms and Monetary Policy - Elena Afanasyeva; Jochen Guentner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper investigates the risk-taking channel of monetary policy on the asset side of banks' balance sheets. We use a factor-augmented vector autoregression (FAVAR) model to show that aggregate lending standards of U.S. banks, e.g. their collateral requirements for firms, are significantly loosened in response to an unexpected decrease in the Federal Funds rate. Based on this evidence, we reformulate the costly state verification (CSV) contract, embed it in a dynamic general equilibrium model, and show that - consistent with our empirical finding - a monetary easing implies an expansion of bank lending for a given amount of borrower collateral. The model also predicts a delayed increase in borrowers' default risk.
Keywords: E44; E52; E32; 330